Qawāʿid al-Tafsīr: The Implementation of Qawāʿid al-Tafsīr in Qur’anic Interpretation Based on the Qur’an and the Sunnah - Ilham Murtala; Andi Miswar; Hamka Ilyas (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Qawāʿid al-Tafsīr constitute essential methodological principles for maintaining the validity of Qur’anic interpretation. Without an appropriate foundational framework, interpretation is at risk of semantic distortion. This study aims to analyze the implementation of Qawāʿid al-Tafsīr in interpretations based on the Qur’an and the Sunnah. The research employs a qualitative method with a library research approach, involving the analysis of classical and contemporary tafsir literature. Data were analyzed descriptively and analytically to identify the application of these principles in interpreting Qur’anic verses. The results indicate that the application of Qawāʿid al-Tafsīr within tafsīr bi al-ma’thūr ensures consistency of meaning, prevents contradictions, and strengthens interpretive validity, particularly through interpreting the Qur’an by the Qur’an, Hadith, and asbāb al-nuzūl. Conclusion: Qawāʿid al-Tafsīr grounded in the Qur’an and the Sunnah represent an essential approach for preserving the accuracy and authenticity of interpretation. Recommendation: Future studies should examine the application of Qawāʿid al-Tafsīr in thematic verses more practically and integrate classical and contemporary approaches to enhance methodological relevance.